Professionalism and Life Dilemma: The Influence of Self-Efficacy and Work-Life Balance on Employee Performance at Coffee Shop in Pontianak City - Helen Hoogendijk; Nova Arestia (LP2M IAIN Palopo, 2026)
This study aims to analyze professionalism and life dilemmas: the influence of self-efficacy and work-life balance on employee performance at coffee shops in Pontianak City. This study uses an associative approach. The research instrument used in data collection was a questionnaire. This study involved 180 respondents as a sample. Sampling was carried out using a saturated sampling technique covering 180 coffee shop employees in Pontianak City. The statistical analysis approach was carried out using the IBM SPSS Statistics 26 program. Data analysis was carried out using validity, reliability, classical assumptions (multicollinearity, heteroscedasticity, normality, linearity), coefficient of determination, multiple linear regression, F-test, and T-test. The findings of the study indicate that (1) self-efficacy and work-life balance simultaneously have a positive and significant effect on employee performance, (2) self-efficacy has a positive and significant effect on employee performance, and (3) work-life balance has a positive and significant effect on employee performance.